EMPLOYEE COMPETENCE, MOTIVATION, AND PERFORMANCE: DOES WORK DISCIPLINE STRENGTHEN RELATIONSHIPS? - Hotima; Ima Andriyani; Rosalina Febrica Mayasari; Sari Sakarina (Universitas Muhammadiyah Bengkulu, 2026)
This study investigates the role of work discipline as a moderating variable in the relationship between competence, motivation, and employee performance among Government Employees with Work Agreements (PPPK) at the Regional Development Planning, Research, and Development Agency of Banyuasin Regency. A quantitative approach using a survey method was employed, involving 48 respondents. Data were collected through Likert-scale questionnaires and analyzed using SmartPLS version 3.2.9. The findings reveal that competence and motivation have a positive and significant effect on both work discipline and employee performance. However, work discipline was not found to significantly moderate the influence of competence and motivation on employee performance. These results suggest that competence and motivation directly affect employee performance without being strengthened or weakened by work discipline. Although this study is limited to a single institution with a relatively small sample size, its findings contribute to the human resource management literature, particularly regarding the limitations of moderating variables, and provide practical insights for government institutions in designing strategies to enhance employee performance.